The concept of General Consent in Switzerland and the implementation at the University Hospital Zurich, a cross-sectional study (Swiss Medical Weekly, 2022)
BACKGROUND: General Consent (GC) allows the further use of health-related data/samples for multiple, unspecified research projects and/or for the collection in databases and biobanks in Switzerland. The application of General Consent in the context of human research is regulated within the scope of the Human Research Act. At the University Hospital Zurich patients are informed about General Consent to which they can agree (GC = yes) or disagree (GC = no) to the use of their routinely collected data/samples in research. In this paper, we investigated the association of demographic and medical factors on a patient’s General Consent choice.METHODS: In this cross-sectional study, we investigated the association of age, gender, number of visits and number of diagnoses on General Consent choice. The study population was stratified by General Consent status group (GC choice: Yes, No, Not issued) and examined by means of descriptive statistics, comparative statistics and a multinomial and logistic regression model. A p-value of 0.001 was determined as significant. RESULTS: The female gender was found to associate with decreased odds in positive General Consent choice (